2013
DOI: 10.1002/etc.2137
|View full text |Cite
|
Sign up to set email alerts
|

Impact assessment of dredging to remove coal fly ash at the Tennessee Valley Authority Kingston Fossil plant using fathead minnow elutriate exposures

Abstract: Abstract-On December 22, 2008, failure of an earthen containment structure resulted in the release of approximately 4.1 million m 3 of coal fly ash into the Emory River and the surrounding area from the Tennessee Valley Authority Kingston Fossil Plant near Kingston, Tennessee, USA. The purpose of the present study was to assess the potential of dredging activities performed to remove the fly ash from the river to result in increased risk to pelagic fish, with special consideration of mobilization of metals. El… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 29 publications
1
8
0
Order By: Relevance
“…The results from this diverse range of studies overwhelmingly indicate that there was no toxicity of the Kingston fly ash in exposures to aquatic organisms inhabiting the overlying water column. Results from an extended ash elutriate study with fathead minnows (Stanley et al ) and an embryo‐larval development study with fathead minnows exposed directly to fly ash (Greeley et al ) further support these findings. These laboratory studies (Table ; Supplemental Data) and a study with amphipod, chironomid, and freshwater mussels exposed to fly ash (Wang et al ) support the finding that the potential toxicity to benthic species (both infaunal and epifaunal) is minimal to moderate, depending on the species and the percentage of ash present in the sediment.…”
Section: Discussionmentioning
confidence: 87%
“…The results from this diverse range of studies overwhelmingly indicate that there was no toxicity of the Kingston fly ash in exposures to aquatic organisms inhabiting the overlying water column. Results from an extended ash elutriate study with fathead minnows (Stanley et al ) and an embryo‐larval development study with fathead minnows exposed directly to fly ash (Greeley et al ) further support these findings. These laboratory studies (Table ; Supplemental Data) and a study with amphipod, chironomid, and freshwater mussels exposed to fly ash (Wang et al ) support the finding that the potential toxicity to benthic species (both infaunal and epifaunal) is minimal to moderate, depending on the species and the percentage of ash present in the sediment.…”
Section: Discussionmentioning
confidence: 87%
“…Otter et al (2012) showed elevated concentrations of arsenic and selenium in various tissues of multiple fish species at ash-associated sites compared to reference sites. Laboratory experiments showed elevated concentrations of arsenic, selenium, and mercury in sediment samples, but no effects on larval or juvenile fathead minnows (Pimephales promelas) when exposed to ash-amended sediment or elutriates (Stanley et al 2013;Greeley et al 2014). When the current body of research on the Kingston spill is viewed collectively, a couple of major observations can be made: (1) The major contaminants of concern appear to be metals, such as arsenic and selenium, and (2) metals associated with ash appear to be largely sediment-bound.…”
Section: Discussionmentioning
confidence: 98%
“…Given the volume of the ash spilled (4.1 million m 3 ), the volume of contaminated sediments dredged (more than 2.6 million m 3 ), and the fluctuations in Emory River discharge during dredging (50-70,000 cfs), issues related to the physical disruption of ashassociated sediments were a concern at the Kingston Fossil spill site. Stanley et al (2013) used an integrated weight of evidence laboratory approach (water chemistry, metal speciation, toxicity, and bioaccumulation) with ash-associated sediments from the Kingston site and concluded that little potential for toxicity to fish existed due to fly ash dredging activities. In the present study, transplanted mussels were used in situ and provided spatially and temporally integrated data (Gunther et al 1999) on the bioaccumulation of metals and overall mussel health (using a mussel health index and weight gain endpoints) at the Kingston site, utilizing pre-and post-dredging deployments.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations